Endothelial Cell Autoantibodies in Predicting Declining Renal Function, End-Stage Renal Disease, or Death in Adult Type 2 Diabetic Nephropathy - Zimering, Mark B. (Frontiers Media S.A., 2014)
Albuminuria is a strong predictor of diabetic nephropathy chronic kidney disease outcomes. Yet, therapeutic albuminuria-lowering has not consistently translated into a reduction in clinical events suggesting the involvement of additional pathogenic factors. Our hypothesis is that anti-endothelial cell autoantibodies play a role in development and progression in diabetic nephropathy. We determined anti-endothelial cell antibody (AECA) bioactivity in protein A-elutes of baseline plasma in 305 participants in the VA NEPHRON-D study, a randomized trial of angiotensin receptor blocker (ARB) or dual ARB plus angiotensin-converting enzyme inhibitor therapy in type 2 diabetes with proteinuric nephropathy. Thirty-eight percent (117/305) of participants had significantly reduced endothelial cell survival ( ≤80%) in the IgG fraction of plasma. A VA NEPHRON-D primary endpoint [end-stage renal disease (ESRD), significant reduction in estimated glomerular filtration rate, or death] was experienced by 58 individuals. In adjusted Cox regression analysis, there was a significant interaction effect of baseline anti-endothelial cell-mediated cell survival and albuminuria on the hazard rate (HR) for primary composite endpoint (P = 0.017). Participants lacking strongly inhibitory antibodies with albuminuria ≥1 g/g creatinine had a significantly increased primary event hazard ratio, 3.41 – 95% confidence intervals (CI 1.84–6.33; P < 0.001) compared to those lacking strongly inhibitory antibodies with lower baseline albuminuria ( <1 g/g creatinine). These results suggest that anti-endothelial cell antibodies interact significantly with albuminuria in predicting the composite endpoint of death, ESRD, or substantial decline in renal function in older, adult type 2 diabetic nephropathy.